EARTHQUAKE DISASTER SHELTER LOCATION PLANNING IN LEMBANG FAULT ZONE AND SHELTER MANAGEMENT STRATEGY USING InaSAFE - AJI NUGRAHA ( NIM : 22412012 ); Pembimbing : DR. Irwan Meilano, S.T, M.Sc ; DR. Irwan Gumela, BISMA
Lesson learned from the Yogyakarta earthquake in 2006 which resulted 5.749 people and 600.000 people were displaced and the Padang earthquake in 2009 which resulted 1.117 people died and 451.000 people were displaced, study to estimating the fatality rate and number of displaced people from a disaster is needed to preparedness or contingency planning. We conducted a study to estimate the number of fatality rate and displaced people from Lembang Fault earthquake source with scenario of 6,6 Magnitude, using InaSAFE software for estimating an impact as a result from a disaster. In this study we also planned shelter locations for evacuating displaced people. The USGSÃ‚Â’s PAGER method is used in InaSAFE software to estimating fatality rate, while to estimate displaced people, it is assumed that population that exposed by V MMI of earthquake intensity will be displaced. In this study to planning of shelter location we use the AHP method to determine the priority of several criteria that considered for finding the suitable locations. The criteria that we used in this study are; landslide prone zone, accessibility, distance from water source, slope, distance to volcano eruption prone zone and the land cover classes. From the results, the estimation of fatality rate in 19 village in Lembang Fault Zone is 1.000 people. The estimation of displaced people is 225.023 people and the estimation of minimum needs for displaced people is 630 tons of rice per week, 3.937.906 liters of drinking water per week, 15.076.542 liters of clean waters per week. The result of expert judgment to suitability of shelter locations is an area of 30,56% of study area has a high suitability score, 56,31% has an intermediate suitability and 13,33% has low suitability.